Understanding Entrepreneur’s Personal Initiative - Ade Irma Anggraeni (Jurnal Akuntansi, Manajemen dan Ekonomi, 2019)
Studies on the personal initiative in the context of entrepreneurship have been in understood better with a variety of perspectives and strategy development. This study aims to examine the effect of goal pursuit and eudaimonic wellbeing on the personal initiative of business owners. Self-regulation perspective in the concept of eudaimonic wellbeing and assimilative mode in concept goal pursuit in use to explore the influence of the two constructs are on the personal initiative of the entrepreneur. This research contributes to clarifying the mechanism for the personal development of entrepreneurs, based on the main characteristics of entrepreneurship in the Indonesian context